Post-Endoscopic Retrograde Cholangiopancreatography Complications at Dr. Cipto Mangunkusumo General Hospital - Rolan Sitompul; Achmad Fauzi; Dadang Makmun; Murdani Abdulah; Ari Fahrial Syam; Marcellus Simadibrata (The Indonesian Society for Digestive Endoscopy, 2009)
Background: This study retrospectively evaluated post-endoscopic retrograde cholangiopancreatography (ERCP) complications at Cipto Mangunkusumo hospital in order to improve management of a subsequent prospective study of post-ERCP complications.Method: The indications, findings, diagnostic or therapeutic procedure, cannulation, devices used during the procedure, and complications of patients treated consecutively with ERCP between January 2004 and November 2008 were evaluated retrospectively.Results: Of 176 ERCP patients who were initially evaluated, 38% had undergone diagnostic ERCP and 62% therapeutic ERCP. The median age of the patients was 49 years (range 18–80 years); 95 (53.9%) were male. Only 54 of these 176 procedures could be evaluated for post-ERCP complications. A computed tomographic abdominal scan or magnetic resonance cholangio-pancreatography was performed in 23 (42.6%) patients and a biliary sphincterotomy in 14 (25.9%) patients. The overall complication rate was 33.3%: 14.8% after diagnostic ERCP and 18.5% after therapeutic ERCP. The complications after diagnostic ERCP were pancreatitis in 3 (15%) patients, cholangitis in 3 (15%) patients, hemorrhage in 1 (5%) patient, pancreatitis and hemorrhage in 1 (5%) patient; the complications after therapeutic ERCP were pancreatitis in 6 (17.6%) patients, cholangitis in 3 (8.8%) patients, hemorrhage in none, and concomitant pancreatitis with hemorrhage in 1 (2.9%) patient. No significant difference was observed between the complication rates and the type of ERCP performed.Conclusion: There were no differences in the complications after diagnostic and therapeutic ERCP. As our study shows the post-ERCP complication rate to be higher than those of other large retrospective and prospective studies, we must evaluate it in a prospective study.Keywords: post-ERCP, complications, therapeutic ERCP, diagnostic ERCP